If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -9 + 5x + 3 = 54 Reorder the terms: -9 + 3 + 7x + 5x = 54 Combine like terms: -9 + 3 = -6 -6 + 7x + 5x = 54 Combine like terms: 7x + 5x = 12x -6 + 12x = 54 Solving -6 + 12x = 54 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 12x = 54 + 6 Combine like terms: -6 + 6 = 0 0 + 12x = 54 + 6 12x = 54 + 6 Combine like terms: 54 + 6 = 60 12x = 60 Divide each side by '12'. x = 5 Simplifying x = 5
| -b^2-13b=0 | | 1/5-10=-25 | | -17x+17=119 | | -2w=70 | | 2(2y-1)=3y+10 | | x-2+4x=6x-9 | | x^3-7x^2-2x-40=0 | | 9x-10+4(x-1)=90 | | 7(6x-5)+11x= | | v=0.2a+0.3b | | 6(w-1)=7(3f+2) | | 3x-2x=3x-2 | | n^2-11n=0 | | v=2a+3b | | X=vt | | X=by | | 10+9x+2x=2-3x | | 8(x-2)=2(3x+8) | | -8(x-2)+4(3-6x)=68 | | 12*x=150 | | -0.25y=8 | | x^5-3x^3-2x=-10 | | 18+60x-180= | | f(x)3x+26=6 | | 7x-3+2(2x-3)=90 | | 12+2x-x=9x+4 | | (8x-9)(7x+4)=0 | | (2*29.95)+(12m)=70.46 | | 3(x+8)=2(4x-3) | | x-8=80 | | n^2+4n-17=0 | | 4*a^2+b-2*a-b^2= |